Uso da adubação nitrogenada, fosfatada e potássica em plantios de Handroanthus heptaphyllus: uma abordagem silvicultural e fisiológica - Berghetti, Álvaro Luís Pasquetti (2020)
The species Handroanthus heptaphyllus is widely distributed in forests in South America and can be cultivated in projects for the provision of ecosystem services and for the production of wood. However, the low fertility of the soil can be a limiting factor, compromising the growth and production of plants. Despite this, native tree forest species are poorly studied in terms of their nutritional demand. Thus, the aim of the study was to identify the influence of the use of different doses of nitrogen (N), phosphorus (P) and potassium (K) on the initial growth and physiological attributes of H. heptaphyllus plants planted in the field. From this, the present thesis was elaborated in three chapters. Chapter I aimed to define the growth and physiological responses in plants of H. heptaphyllus submitted to nitrogen fertilization after planting. This study was developed by testing five doses of N (0, 45, 90, 180 and 270 kg ha-1) in three vegetative phases of the plants (6, 12 and 18 months after planting). In Chapter II, the influence of P doses, on the growth and on the physiological attributes of H. heptaphyllus plants was verified. The treatments tested in this study were five doses of P (0, 45, 90, 180 and 270 kg of P2O5 ha-1) evaluated at 6, 12, 18 and 24 months after planting, in a split-time scheme. In Chapter III, the morphological and physiological characteristics of Handroanthus heptaphyllus plants submitted to K doses in the field were investigated. In this work, five doses of K (0, 25, 50, 100 and 150 kg of K2O ha-1) were evaluated in a split-time scheme (6, 12, 18 and 24 months after planting). The experiments were carried out in random blocks with four replications. Each experimental unit consisted of 24 plants, with eight plants being evaluated. In general, it is evident that for the species H. heptaphyllus nitrogen fertilization, phosphate and potassium does not cause a significant effect on the growth of the plants right after planting, however, it is noticed that the species responds positively to the increase in the N content , P and K from the 12th month after planting. The addition of these three nutrients to the soil is able to increase their concentration in plant leaves, increasing photosynthetic pigments, light absorption and efficiency in the photochemical process. Furthermore, the results indicate that the use of 260.0 kg N ha-1 kg divided into 35% of the dose added in covetas at planting; 32.5% three months after the first application; and the remainder in the sixth month after planting provides H. heptaphyllus with greater growth in height and diameter of the collection at 18 months after planting. The use of 190 kg P2O5 ha-1 and 72 kg K2O ha-1 in planting provides greater metabolic activity, utilization of light energy and, consequently, height and diameter of the plant collection. Nitrogen, phosphate and potassium fertilization is an essential strategy for the cultivation of H. heptaphyllus, capable of improving nutritional status and accelerating plant growth.